Cultural and institutional barriers among data stewards regarding data access for research - Teng, Jack; McGrail, Kim (International Journal of Population Data Science, 2018)
Introduction In British Columbia, the rules and procedures that data stewards follow to adjudicate data access requests (DAR) vary considerably. These variations can lead to discrepancies in the speed at which DARs are processed. With complex DARs involving numerous data stewards and data sets, the request may take over a year Objectives and Approach Our main goal was to understand the institutional and cultural factors that influence data stewards when processing a DAR. We wished to see in particular if risk aversion was playing a role when making decisions about data access. We interviewed 24 people representing 21 organizations in British Columbia. Most were data stewards, but we also interviewed people processing the data requests and also privacy advisors. Results We found that organizations varied greatly in terms of their skills and expertise regarding the rules and procedures around processing DARs. In particular, data stewards noted that they experienced differences in interpreting legislation, resulting in disagreements when they were working with other data stewards. In terms of risk aversion, data stewards stated they wished to encourage research, but in some cases followed unclear rules. Nearly all noted that there is little guidance provided for the job of “data steward” and either no or very little training when taking on these positions. Conclusion/Implications While there may be stated governmental policies promoting that linked data be used for research, ultimately it is the data stewards approving DARs that will determine access to data. Understanding how and why they make those decisions will help better implement data access policies.